2014
DOI: 10.5586/asbp.1982.031
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lead on the development of lupin seedlings and ultrastructural localization of this metal in the roots

Abstract: The effect of lead on the early phases of development of yellow lupin seedlings was investigated. In the presence of this metal the number of germinating seeds was found to diminish distinctly, the hypocotyls and roots were shorter and the fresh weight and anthocyanin content in the cotyledones were markedly decreased. In the root cap cells lead was present in the vacuoles, ER, dictyosomes, the nuclear envelope and cell walls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The distribution of lead deposits in the meristematic cells of A. cepa roots was similar to that described by other authors (Gzyl et al 1997; Wierzbicka 1995; Woźny et al 1982). Great number of lead deposits in cell walls and vacuoles confirms that this metal is neutralised by immobilisation in those structures (Krzesłowska et al 2010; Wierzbicka 1995, 1998).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The distribution of lead deposits in the meristematic cells of A. cepa roots was similar to that described by other authors (Gzyl et al 1997; Wierzbicka 1995; Woźny et al 1982). Great number of lead deposits in cell walls and vacuoles confirms that this metal is neutralised by immobilisation in those structures (Krzesłowska et al 2010; Wierzbicka 1995, 1998).…”
Section: Discussionsupporting
confidence: 90%
“…Lead deposits were noticed predominately in the cell walls, where they were apparently chelated and bound tightly with middle lamellar polysaccharides as it had been reported previously (Antosiewicz and Wierzbicka 1999; Krzesłowska et al 2009; Tung and Tample 1996; Wierzbicka 1998). Plant cell wall is regarded as one of the main sites for lead deposition and detoxification (Baranowska-Morek and Wierzbicka 2004; Jarvis and Leung 2002; Wierzbicka 1987a, b, 1998; Woźny et al 1982). The occurrence of lead deposits in dictyosomal vesicles, endoplasmic reticulum or plasmalemma observed in the examined material is also connected with the mechanisms of metal exclusion from cell metabolism (Wierzbicka 1995, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, different concentrations of cadmium chloride (CdCl 2 ) decreased the germination percentage and the germination rate index (GRI) of cowpea (Vigna unguiculata L.) (AI-Rumaih et al 2001). Similarly, the inhibitory and toxic effects of lead on the germination of seeds of Lupinus luteus (Wozny et al 1982) and pea (Pisum sativum) (Wierzbicka and Obidzinska 1998) and cadmium on pea (Smiri 2011) are reported. In yet another study, Atici et al (2005) observed that lead and zinc significantly delayed and impeded the germination of chickpea (Cicer arietinum cv.…”
Section: Legume Germination Under Metal Stressmentioning
confidence: 99%